Implementation of Islamic Business Ethics to the Progress of Egg Roll MSME Traders in Waru District - Imroatun Mufida; Choirun Nisa; Dewi Lara sati; M. Daimuddin; Abdur Rohman (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
Micro, Small and Medium Enterprises (MSMEs) are one effort to overcome society's economic problems. When doing business, MSMEs often face challenges in running their business. The purpose of research on the application of Islamic business ethics to the progress of MSME traders, this type of research uses descriptive qualitative research, the object of research is  egg rolls located in the Waru District area, this research uses two types of data, namely data primary and secondary data. The results of this study show the application of Islamic business ethics to MSME traders applying an honest nature which will bring benefits to themselves and others in doing business.